PERLINDUNGAN DESAIN INDUSTRI BAGI UMKM YANG BERKEADILAN SOSIAL - Sukarmi Sukarmi (UNISSULA, 2016)
The setting of Industrial Design in Indonesia is the result of transplantation of TRIP’s Agreement and Paris Convention for the Protection of Industrial Property (Paris Convention) the capitalist paradigm. These regulations are difficult to implement optimaly, because of the different of the values and cultures background. However, due to the juridical and psychological consequences, Indonesia h a s agreed GATT (General Agreement on Tariffs and Trade) and also agreed framework of the GATT/ WTO (World Trade Organization), Indonesia finally ratified through Law No. 7 Year l994. The great hope of Industrial Design Act can be implemented, but the fact the contrary Law No. 31 of 2000 is still not optimal effect mainly by SMEs. It is evident the longer the number of applicants was even more reduced due to the degradation of Creativity and do not meet the values of social justice. It is prove that the number of applicants was even more reduced due to the degradation of Creativity and do not meet the values of social justice. Alternative step in bridging is done internalization of the values of Pancasila into the Industrial Design Act as “a spirit or soul” that is expected to provide justice for the designer (SMEs), further, it can development of creativity.